C = 5/9(F-32) is the conversion from Fahrenheit to Celsius.

We want

F = 3C = 3(5/9)(F-32) (substitute for C)

F = 5/3(F-32) (reduce the fraction)

3F = 5(F - 32) (multiply by 3)

3F = 5F - 160 (use the distributive property)

0 = 2F - 160 (subtract 3F)

160 = 2F (add 160)

80 = F (divide by 2)

C = 5/9(80 - 32) = 5/9*48 = 240/9 = 26 2/3

We want

F = 3C = 3(5/9)(F-32) (substitute for C)

F = 5/3(F-32) (reduce the fraction)

3F = 5(F - 32) (multiply by 3)

3F = 5F - 160 (use the distributive property)

0 = 2F - 160 (subtract 3F)

160 = 2F (add 160)

80 = F (divide by 2)

C = 5/9(80 - 32) = 5/9*48 = 240/9 = 26 2/3